A long non‐coding RNA GATA6‐AS1 adjacent to GATA6 is required for cardiomyocyte differentiation from human pluripotent stem cells. Issue 11 (4th September 2020) - Jha, Rajneesh; Li, Dong; Wu, Qingling; Ferguson, Katherine E.; Forghani, Parvin; Gibson, Gregory C.; Xu, Chunhui
Abstract: Long noncoding RNAs (lncRNAs) are crucial in many cellular processes, yet relatively few have been shown to regulate human cardiomyocyte differentiation. Here, we demonstrate an essential role of GATA6 antisense RNA 1 ( GATA6‐AS1) in cardiomyocyte differentiation from human pluripotent stem cells (hPSCs). GATA6‐AS1 is adjacent to cardiac transcription factor GATA6 . We found that GATA6‐AS1 was nuclear‐localized and transiently upregulated along with GATA6 during the early stage of cardiomyocyte differentiation. The knockdown of GATA6‐AS1 did not affect undifferentiated cell pluripotency but inhibited cardiomyocyte differentiation, as indicated by no or few beating cardiomyocytes and reduced expression of cardiomyocyte‐specific proteins. Upon cardiac induction, the knockdown of GATA6‐AS1 decreased GATA6 expression, altered Wnt‐signaling gene expression, and reduced mesoderm development. Further characterization of the intergenic region between genomic regions of GATA6‐AS1 and GATA6 indicated that the expression of GATA6‐AS1 and GATA6 were regulated by a bidirectional promoter within the intergenic region. Consistently, GATA6‐AS1 and GATA6 were co‐expressed in several human tissues including the heart, similar to the mirror expression pattern of GATA6‐AS1 and GATA6 during cardiomyocyte differentiation. Overall, these findings reveal a previously unrecognized and functional role of lncRNA GATA6‐AS1 in controlling human cardiomyocyte differentiation.